Juri Muri Around Slovenia: Poetry as a Cultural Heritage Guide - Bale, Norma; Haramija, Dragica (Slavistična prepletanja 6, 2025)
The picture book Juri Muri Around Slovenia (2011) by poet Tone Pavček and illustrator Damijan Stepančič is the third poem in the tetralogy about Juri and Bongo. The eight-part narrative poem or humorous tale in rhyme simultaneously develops numerous story lines. The material covers natural as well as cultural-historical sites in Slovenia, deals with the themes of friendship and mutual respect, travel, studying local history, finding out about foreign lands, and love. The main events take place in a chronological order with intermittent leaps that relate to ethnographic characters (Kurent, Zeleni Jurij), persons from cultural history (Prešeren) or professional groups (büraši), as well as spaces (the landscape of Slovenia, towns, mountains, rivers, famous buildings, monuments, etc; Africa), animals (Ljubljana Zoo, African animals), events (traditional events such as the carnival Kurentovanje). The picture book contains several symbols that are mentioned in the text and depicted in the illustrations.